Evaluating patient education resources for supporting treatment decisions in latent tuberculosis infection. (August 2021) - Clarke, Amy L; Sowemimo, Tamilore; Jones, Annie SK; Rangaka, Molebogeng X; Horne, Rob
Objective: People with latent tuberculosis infection (LTBI) are required to make complex treatment decisions, which require an understanding of personal risk and associated benefits. However, many people with LTBI in the United Kingdom are at risk of low health literacy and can also experience language barriers, which can affect decision making. Patient education resources can support understanding but must meet the needs of the target population. The aim of this study was to evaluate the accessibility, readability and content of LTBI patient education resources. Design: Review and descriptive analysis of online LTBI patient education resources. Setting: UK-based online patient education resources. Method: We searched UK public health and charitable organisations for online LTBI patient education resources. Resources were evaluated in terms of accessibility (availability of translated versions); readability (Flesch–Kincaid Reading Ease [FKE], Flesch–Kincaid Grade Level [FKG] and Simplified Measure of Gobbledygook [SMOG]), theoretical content (Extended Common-Sense Model) and principles of shared decision making. Results: Seventeen out of 60 articles identified in the search met the prespecified criteria for inclusion. Translated materials were available for 7 of them. The overall mean ± SD readability scores and corresponding reading ages were FKE 63.51 ± 8.81 (13–15 years), FKG 9.14 ± 8.95 (13–15 years) and SMOG 8.27 ± 1.51 (13–14 years). No resources met Health Education England recommended readability levels for health-related information. Dimensions of cognitive representations of illness and treatment most commonly addressed included treatment control, cause and identity (symptom and label); no resources addressed emotional identity. Conclusion: Current and future LTBI patient education resources would benefit from greater consideration of the needs of non-English language speakers, readability and theoretical content to improve patient illness experience and support informed treatment decision making.